Water and solute transport across the peritoneal membrane. Issue 5 (September 2015) - Morelle, Johann; Devuyst, Olivier
Abstract : Purpose of review: We review the molecular mechanisms of peritoneal transport and discuss how a better understanding of these mechanisms is relevant for dialysis therapy. Recent findings: Peritoneal dialysis involves diffusion and osmosis through the highly vascularized peritoneal membrane. Computer simulations, expression studies and functional analyses in Aqp1 knockout mice demonstrated the critical role of the water channel aquaporin-1 (AQP1) in water removal during peritoneal dialysis. Pharmacologic regulation of AQP1, either through increased expression or gating, is associated with increased water transport in rodent models of peritoneal dialysis. Water transport is impaired during acute peritonitis, despite unchanged expression of AQP1, resulting from the increased microvascular area that dissipates the osmotic gradient across the membrane. In long-term peritoneal dialysis patients, the fibrotic interstitium also impairs water transport, resulting in ultrafiltration failure. Recent data suggest that stroke and drug intoxications might benefit from peritoneal dialysis and could represent novel applications of peritoneal transport in the future. Summary: A better understanding of the regulation of osmotic water transport across the peritoneum offers novel insights into the role of water channels in microvascular endothelia, the functional importance of structural changes in the peritoneal interstitium and the transport of water and solutes across biological membranes in general.